Determinants of Toddlers’ History with Stunting Incidence in the Coastal Community - Dolang, Mariene Wiwin; Pelamonia, Anastasya; Simanjuntak, Yohanes Friyedo (Window of Health : Jurnal Kesehatan, 2024)
The main nutritional problem in toddlers that is still commonly found in many countries around the world is stunting. Stunting is a chronic nutritional problem caused by long-term malnutrition. Infectious diseases and malnutrition can cause stunting. The aim of the study was to determine the relationship between the history of children and the incidence of stunting in the people of the Coastal Village of Kamarian. This research is an analytic survey research with a cross sectional design. This research was carried out on June 1 -31 2022. The sample in this study was 113 toddlers aged 2-5 years using total sampling. This study uses the Chi-Square test. The results showed that there were 22.9% (27 children) who were stunted. There is a relationship between birth weight (ρ=0.000), exclusive breastfeeding (ρ=0.013), infectious diseases (ρ=0.000), complementary feeding (ρ=0.002) and stunting. Low birth weight, exclusive breastfeeding, infectious diseases, and early complementary feeding (MP-ASI) can affect the incidence of stunting in children.